If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) = 2x + -8 Reorder the terms: 2(-3 + y) = 2x + -8 (-3 * 2 + y * 2) = 2x + -8 (-6 + 2y) = 2x + -8 Reorder the terms: -6 + 2y = -8 + 2x Solving -6 + 2y = -8 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2y = -8 + 6 + 2x Combine like terms: -6 + 6 = 0 0 + 2y = -8 + 6 + 2x 2y = -8 + 6 + 2x Combine like terms: -8 + 6 = -2 2y = -2 + 2x Divide each side by '2'. y = -1 + x Simplifying y = -1 + x
| 7st+4t(t+s+4)-9t= | | 2.50+1.5(m-1)=17.50 | | 110d=115d+45 | | 4/6=x/11 | | 13r-39=10r | | 6x+5x-x= | | 65+k=8 | | 9x-5-14=17 | | (x-2)2=49xiswhat | | y=x^2-6x+9forx | | y=x^2-6y+9 | | 14lnx=17 | | 585=X^2 | | x+17+8=25 | | 3x(2x+40)=180 | | 5y^2+10y-120=0 | | 6(2x+y)= | | -3/2=2x^2 | | 2(x+5)=90 | | -3=1/2x-4 | | 2s^2-s-10=0 | | 1/4k=3(-1/4k+3) | | 1x-6=9 | | (.1x-33)+(.4x-40)=180 | | x=2x-132 | | (-3x+79)= | | 7st+4t(t+s+4)-9= | | x+7-4=-15 | | 300=-(420*600*1500)-(-1c*600*1500)-(1000*600*1500) | | -14+3x=11 | | 3u-8=-20 | | -10y=x+21 |